2013
DOI: 10.1007/s00595-013-0629-y
|View full text |Cite
|
Sign up to set email alerts
|

Primary and secondary adenocarcinomas associated with anal fistulae

Abstract: Anal fistulae are commonly seen in the coloproctology clinic, but special attention to similar conditions associated with malignant disease is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…As Rosser first established in 1934, these cancers are often associated with a prolonged history of chronic fistula disease greater than 10 years [ 2 ]. Recently, however, cases where the fistula has been present for less time are being reported, in some cases being diagnosed after 2 months [ 3 ]. In this particular case, mucinous adenocarcinoma was diagnosed only 4 months after the fistula.…”
Section: Discussionmentioning
confidence: 99%
“…As Rosser first established in 1934, these cancers are often associated with a prolonged history of chronic fistula disease greater than 10 years [ 2 ]. Recently, however, cases where the fistula has been present for less time are being reported, in some cases being diagnosed after 2 months [ 3 ]. In this particular case, mucinous adenocarcinoma was diagnosed only 4 months after the fistula.…”
Section: Discussionmentioning
confidence: 99%
“…Anal adenocarcinoma is a rare malignancy of the anal canal 52 . Owing to its rarity, the optimal treatment strategy for anal adenocarcinoma has not been established, there is very little evidence to guide treatment, and most are treated like low rectal cancers.…”
Section: Special Casesmentioning
confidence: 99%
“…Perianal fistula associated adenocarcinoma has also been reported in Crohn's disease [4]. Yamada K.et al [5] there is a need for special attention to be given to the similar conditions associated with malignant disease. for Andrew T. study [6] showed that fistulae result from perianal Crohn's disease, tuberculosis, or neoplasm.…”
Section: Introductionmentioning
confidence: 97%